Applications of X-Ray Computed Tomography in Particulate Systems - C. L. Lin; J. D. Miller; A. Cortes (KONA Powder and Particle Journal, 2014)
X-ray computed tomography (CT) is an ideal technique for investigating the internal structure of multiphase materials in a noninvasive and nondestructive manner. CT technology used in conjunction with specialized algorithms and advanced computer facilities can be used to provide quantitative information in addition to being an ideal medium for scientific visualization. This paper reviews some advanced reconstruction algorithms and examines two cases in which CT has been successfully used: (1) coal washability analysis and (2) density gradient determination in an air-sparged hydrocyclone (ASH) flotation.